Systems-level understanding of copper effect in Saccharomyces cerevisiae - Öç, Şebnem. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Copper is a crucial trace element for all living systems as it is required for the proper functioning of several biological processes. Copper homeostasis, which governs the mechanisms of copper uptake, delivery, utilization, and export, is impaired in a variety of human diseases which underscores the importance of the balancing of the intracellular copper levels. High similarity of the copper homeostatic systems in yeasts and humans makes Saccharomyces cerevisiae an ideal eukaryotic model organism for the studies related to copper transport. In this thesis, the effect of copper on yeast cells was investigated through integrative systems biology approaches. The dynamic transcriptomic response of the mutant cells lacking the copper transporter gene CCC2 as well as HO deleted cells, as reference, were evaluated based on the transcriptional changes in genome scale. Considering the fact that perturbation response experiments enables understanding of the dynamic changes as well as response mechanisms within the cells, copper impulse experiments were performed in order to investigate the copper effect. The strains were grown in chemostat cultures under copper deficient conditions, and copper is introduced into the media in excess amount which is not toxic. The investigation of the dynamic transcriptional profiles of the strains gave insight into the alterations in various biological processes including stress response, sulfur compound metabolism, DNA repair, and respiratory complex biogenesis as well as copper and iron homeostasis, in response to copper which differed between the strains especially as of the fifth minute. The identification of the significantly correlated paths within the reconstructed copper sensing network indicated possible involvement of several proteins in copper sensing and/or transport, and also indicated that copper homeostasis is controlled in mRNA level, and mRNA decay pathways may have central role in this regulation.
Keywords: Saccharomyces cerevisiae.; Copper.